DEVELOPMENT OF COMMUNICATIVE COMPETENCE OF FUTURE TEACHERS IN THE PROCESS OF PEDAGOGICAL EDUCATION - Usmonova , Maftunaxon Qaxramonjon qizi (Educational Research in Universal Sciences, 2024)
The article focuses on the innovative methods of formation and development of communicative competence of students through various assignments in English classes.